Make, family projects for smart objects : tabletop projects that respond to your world - Keefe, John (Maker Media, 2016)
"The Internet of Things" is the new buzzphrase, but what is it? A toaster that texts? The fitness band on your wrist? The camera in an infant's room? Sure, it's all of those things. But it's also your phone: an ultra-sophisticated sensor and communications system in your pocket or purse--capable of tracking your steps, capturing an image, or calling an Uber. And it is actually not hard or expensive to make a sensing, communicating object yourself. Doing so can be rewarding, fun, and even useful. This book teaches the basics of building sensors and communicating objects through a series of practical, demonstrative, and fun activities